A Poly(pyrrole-3-carboxylic acid) Thin Film Modified Screen Printed Carbon Electrode as Highly Sensitive and Selective Label-free Electrochemical Immunosensing Platform - Supakiet Chanarsa (Faculty of Science, Chiang Mai University, 2020)
Chiang Mai Journal of Science